Criteria for inferring legal objectives in financial transactions: A study of models - Abdessamad, Belhadji (The International tax journal, 2025)
This study highlights the importance of applying legal objectives in contemporary jurisprudential efforts. However, this application is not unrestricted: researchers have imposed a set of regulations to ensure that the implementation of these objectives aligns with legal texts rather than serving as a means to undermine or evade legal rulings under the pretext of interests.